Exploring the determinants of social entrepreneurial intentions: Evidence from India - kumari, Preeti; Satpal (International Journal of Psychosocial Rehabilitation, 2020)
Social Entrepreneurship is a practice and a field of scholarly investigation these days. Academics and non-profit organizations have grown increasingly interested in social entrepreneurship over the years. Many different practitioners have held discussions on these subjects from different angles. This paper shed a light on the background and the present composition of discussions on these topics. The aim of the present study is to explore the determinants of social entrepreneurship intentions. To attain this objective, we have collected the data from students of MBA final year who have intent to become a social entrepreneur. In addition, this article is based on responses of 355 students. We used MS Excel and SPSS V.24 to analyze the data. Our results provided that empathy have significant predictor of social entrepreneurial intentions. In addition, our findings documented that social entrepreneurial self-efficacy, perceived social support, moral obligation are significant predictors of social entrepreneurial intent (SEI). Some of the findings are consistent with previous research. Therefore, our findings provide useful insight to multiple stakeholders.